Why Be One Protein When You Can Affect Many? The Multiple Roles of YB-1 in Lung Cancer and Mesothelioma - Johnson, Thomas G.; Schelch, Karin; Mehta, Sunali; Burgess, Andrew; Reid, Glen (Frontiers in Cell and Developmental Biology, 2019)
Lung cancers and malignant pleural mesothelioma (MPM) have some of the worst five year survival rates of all cancer types, primarily due to a lack of effective treatment options for most patients. Targeted therapies have shown some promise in thoracic cancers, although efficacy is limited only to patients harboring specific mutations or target expression. Although a number of actionable mutations have now been identified, a large population of thoracic cancer patients have no therapeutic options outside of first-line chemotherapy. It is therefore crucial to identify alternative targets that might lead to the development of new ways of treating patients diagnosed with these diseases. The multifunctional oncoprotein Y box binding protein-1 (YB-1) could serve as one such target. Recent studies also link this protein to many inherent behaviors of thoracic cancer cells such as proliferation, invasion, metastasis and involvement in cancer stem-like cells. Here, we review the regulation of YB-1 at the transcriptional, translational, post translational and sub-cellular levels in thoracic cancer and discuss its potential use as a biomarker and therapeutic target.